Asymmetric effects of inflation rate changes on the stock market index : The case of Indonesia - Sia, Peck Ching; Leong, Choi Meng; Puah, Chin Hong (Centre of Sociological Research in co-operation with University of Szczecin (Poland), Academy of Economic Studies in Bucharest (Romania) and Széchenyi István University (Hungary)., 2023)
Over the years, macroeconomic fundamentals and the stock market were found to have symmetrical relationship in numerous scientific investigations. These fundamentals provide crucial knowledge regarding stock price indices by providing forecasts for the future and information on the current status of the economy. This study employs a Nonlinear Autoregressive Distributed Lags (NARDL) model to fill in the research gap by estimating the asymmetric relationship between inflation and stock market from 1996 to 2020. The study suggests that inflation has a long-run and short-run asymmetric affect on the stock price, while both positive and negative inflation changes harm stock prices. As it reveals, the asymmetric impact of inflation on the stock market, this study can assist investors and businesses in making well-informed decisions that result in a more efficient allocation of resources, ultimately benefiting the economy. Additionally, policymakers can utilize these findings to design effective strategies for managing inflation, stabilizing prices, promoting economic growth, and ensuring financial market stability